Monitoring and Genesis Analysis of Surface Deformation in Shenxianpo Coal Mine, Liupanshui Using SBAS-InSAR Technology (Journal of science and technology exploration, 2026)
The karst landscape of Guizhou is notably developed, with complex geological conditions where surface deformation often exhibits characteristics of concealment, abruptness, and nonlinearity. Traditional ground-based monitoring methods are limited by terrain and accessibility, making it difficult to achieve comprehensive coverage of the study area. Differential interferometric radar technology is prone to interference from temporal-spatial decorrelation and atmospheric errors under complex topographic conditions. Based on 54 scenes of Sentinel-1A satellite data from the Shenxianpo Coal Mine in Liupanshui, this study applied the Small Baseline Subset Interferometric Synthetic Aperture Radar (SBAS-InSAR) technique to analyze the time-series characteristics of surface deformation. The results indicate that during the period from January 12, 2023, to January 1, 2025, the mining area exhibited a non-uniform subsidence trend from west to east, with a maximum cumulative subsidence of approximately 138 mm and a maximum subsidence rate of about 62 mm/a. As mining activities continued, surface subsidence showed an accelerating trend, and the affected area gradually expanded, revealing a significant correlation between mining intensity and surface deformation. This study verifies the efficiency and reliability of the SBAS-InSAR technique in monitoring surface deformation in mining areas, providing a reference case for early warning of geological hazards and safety management in similar mining regions in southwestern China.
Keywords: SBAS-InSAR; Mining-induced deformation; Time-series displacement analysis; Subsidence depression